2011
DOI: 10.1073/pnas.1019668108
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane orientation and possible role of the fusogenic peptide from parainfluenza virus 5 (PIV5) in promoting fusion

Abstract: Membrane fusion is required for diverse biological functions ranging from viral infection to neurotransmitter release. Fusogenic proteins increase the intrinsically slow rate of fusion by coupling energetically downhill conformational changes of the protein to kinetically unfavorable fusion of the membrane-phospholipid bilayers. Class I viral fusogenic proteins have an N-terminal hydrophobic fusion peptide (FP) domain, important for interaction with the target membrane, plus a C-terminal transmembrane (C-term-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 82 publications
6
86
3
Order By: Relevance
“…In its final stage, fusion is then believed to progress through a mechanism where the N-and C-terminal helices of multiple hemagglutinin trimers zipper together in an antiparallel fashion to form a competent fusion pore (20). Opening of the fusion peptide therefore appears a requisite step for adopting a helical structure that is sufficiently long to traverse the lipid bilayer, which is needed to allow formation of the stipulated oligomeric fusion pore structure, assembled from fusion peptides and HA2 C-terminal transmembrane helices (38).…”
Section: Discussionmentioning
confidence: 99%
“…In its final stage, fusion is then believed to progress through a mechanism where the N-and C-terminal helices of multiple hemagglutinin trimers zipper together in an antiparallel fashion to form a competent fusion pore (20). Opening of the fusion peptide therefore appears a requisite step for adopting a helical structure that is sufficiently long to traverse the lipid bilayer, which is needed to allow formation of the stipulated oligomeric fusion pore structure, assembled from fusion peptides and HA2 C-terminal transmembrane helices (38).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Donald et al (5) present analytical ultracentrifugation results showing that the parainfluenza virus 5 (PIV5) fusion peptide assembles into hexamers in dodecylphosphocholine micelles. Minimal evidence was found for other multimeric states.…”
Section: New Data On Parainfluenza Virus Fusion Assembliesmentioning
confidence: 99%
“…Studies with class I vFMGs have shown that insertion of synthetic, soluble fusion peptides into the membrane can deform the lipid bilayer (48) and induce membrane fusion (49). Paramyxovirus fusion peptides derived from the PIV5 F protein were demonstrated to associate into a helical transmembrane bundle in lipid bilayers; this bundle interacts tightly with the corresponding PIV5 F transmembrane domains and forms a thermodynamically favorable coiled-coil in the lipid phase (13). In analogy to cellular SNARE proteins (50), this zippering of the F-protein helix in the bilayer -equivalent to the formation of the four-helix bundle in the SNARE transmembrane domain-may extend the water-soluble 6HB fusion core into the membrane and contribute part of the energy required to drive fusion (13).…”
Section: Discussionmentioning
confidence: 99%
“…Paramyxovirus fusion peptides derived from the PIV5 F protein were demonstrated to associate into a helical transmembrane bundle in lipid bilayers; this bundle interacts tightly with the corresponding PIV5 F transmembrane domains and forms a thermodynamically favorable coiled-coil in the lipid phase (13). In analogy to cellular SNARE proteins (50), this zippering of the F-protein helix in the bilayer -equivalent to the formation of the four-helix bundle in the SNARE transmembrane domain-may extend the water-soluble 6HB fusion core into the membrane and contribute part of the energy required to drive fusion (13). Critical functional interactions between fusion peptides and transmembrane domains also were reported for influenza virus HA (45) and HIV-1 gp41 (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation